Phytoplankton community composition in mussel farms of Villareal Bay, Samar from November 2018 to March 2019. - Atis, Hanna R. (Hanna R. Atis, 2019)
Villareal Bay is one of the top producers of green mussels in Region 8. Many of the locals depend on the bay for livelihood, through shellfish cultivation. Phytoplankton are primarily consumed by marine organisms such as the green mussel (Perna viridis). The BFAR monitors the red-tide causing dinoflagellate Pyrodinium bahamense in the bay. But P. bahamense is only one of the many potentially harmful phytoplankton. No study has been done regarding other phytoplankton in general in the area. Assessment of the phytoplankton community can provide an insight to the water quality of Villareal bay and contribute to the knowledge of ecology of tropical phytoplankton in general. This study aimed to document the phytoplankton community present in the area. The phytoplankton were collected using a 1m length 20um mesh size plankton net with 30 cm diameter and a bucket. There were 39 genera and 52 species of phytoplankton observed from November 2018 to March 2019. The average cell density of the bay was 123.52 x 10 raised to the power of 4 cells/L. The highest value for the phytoplankton diversity, evenness and richness were 3.35, 0.84 and 0.48 respectively. The most common genera were Noctiluca, Chaetoceros, Thalassionema, Rhizosolenia, and Cylindrotheca. The highest cell density recorded was in March with 580 x 10 raised to the power of 4 cells/L which was due to Noctiluca. Noctiluca was present in all sampling stations and dominated the months of December, January and March. A Noctiluca bloom is indirectly linked to prey abundance because it grazes on other phytoplankton and may compete with P. viridis. There were at least seven potentially harmful phytoplankton found in the bay and are discussed in the paper.